A dynamic web based color image encryption using Latin square image cipher - sugamya, Katta; pabboju, Suresh; Vinay Babu, A (International Journal of Engineering and Technology, 2018)
A new Latin square image encryption provide a new way of integrating probabilistic encryption in image by embedding random noise in the least significant image bit-plane . LSIC may achieve many desired properties of a secure cipher including a large key space, high key sensitivities, uniformly distributed cipher text, semantically secure, and robustness against channel noise.Â